Terms of endearment in English: affection and tenderness in the Historical Thesaurus of the Oxford English dictionary online - Landmann, Julia (English today, 2022)
Terms of endearment enjoy great popularity in all languages to express feelings such as affection and tenderness. The present paper concentrates on the use of these types of words in English. The Historical Thesaurus of the Oxford English Dictionary (henceforth the HTOED) serves as a valuable tool to identify the plethora of terms of endearment which became established in English over the centuries.